The leadership triad knowledge, trust, and power - Zany, Dale E. (Oxford University Press, 1997)
In this concise, insightful volume, Zand dispels the mystery of leadership so that managers at all levels - from the CEO to first-line supervisor - can understand the key concepts of leadership and develop the skills needed to lead effectively. Zand cogently examines the three essential elements of high-performance leadership: knowledge, trust, and power.